CCTV from light to pixels - Damjanovski, Vlado 1956- (Butterworth-Heinemann, 2014)
The new edition of CCTV, a high-level professional reference, is expanded to cover all video compression techniques used in the ever-increasing assortment of digital video recorders (DVRs) available on the market today. In addition to demystifying DVR technology, the third edition also clarifies the technology of data networking and explains various compression techniques. Along with all this, the book retains the particulars that made the previous editions convenient and valuable, including details of CCD cameras, lenses, coaxial cables, fiber-optics, and system design